Pembuatan Neon Box Berbasis Panel Surya sebagai Pemanfaatan Energi Mandiri di SMK Negeri 2 Pengasih Kulon Progo - Arya Yusuf; Wahyu Karunia Putra; Alfian Rizky Hikmawan; Muhammad Fatchurrohman (Jurnal Pengabdian KOLABORATIF, 2024)
Innovative Independent MBKM activities are initiations and efforts to facilitate student learning rights in self-development to improve student competence by skill and knowledge in the fields of Education, Industry, Society, Entrepreneurship, and Research. Students carry out Innovative Independent MBKM activities through Educational Practices at one of the SMKs in Kulon Progo. SMK Negeri 2 Pengasih is a superior vocational high school in the Kulon Progo region which is the destination for carrying out Educational Practices activities. This school does not have technology for the utilization of renewable technology. Neon boxes are made by involving observation, design, working process, trial, and job evaluation. The purpose of creating a neon box is to reduce dependence on conventional energy sources, generate long-term cost savings, and decrease the carbon footprint. Through the neon box innovation, the results were obtained that this tool can integrate solar panel technology as independent energy utilization.